Observer-based control of vertical penetration rate in rotary drilling systems. (October 2021) - Faronov, Maksim V.; Polushin, Ilia G.
Abstract: An algorithm for regulation of the vertical penetration rate in rotary drilling systems is developed under the assumption that parameters of the rock-bit interaction as well as those of the translational dynamics are unknown. The control design utilizes a multi-step approach, where the vertical penetration velocity is regulated through an appropriate assignment of a reference rotational velocity signal, while the tracking of the latter is achieved using tracking with disturbance rejection scheme. In contrast with the existing results, the algorithm does not require real-time measurement and communication to the ground level of the downhole variables, such as angular position, rotational velocity, and torque-on-bit. This is achieved through the use of high-order sliding mode observers which estimate the required downhole variables based on measurements performed at the ground level. Simulation results are presented which confirm efficiency of the proposed control method. Highlights: Algorithm for regulation of vertical penetration rate in rotary drilling systems. Parameters of rock-bit interaction and translational dynamics are unknown. Real-time communication between downhole and ground levels is not required. Downhole variables are estimated using high-order sliding mode observers. Multi-step approach: speed-gradient control, disturbance rejection, cascaded system.